Bridging the Digital Divide in Rural India: Lessons from a Survey in Four States. (April 2013) - Singh, Nirvikar; Zhou, Yan; Williams, Kristen; Kendall, Jake; Kaushik, P.D.
The focus of this article is an alternative policy approach to bridging the digital divide, through organisational innovations that provide low cost Internet access in rural India. We use survey data from 500 individuals in four states of India: Haryana, Madhya Pradesh, Punjab and Rajasthan, to examine factors influencing patterns of computer and Internet use. We estimate logit and multinomial logit models, using microeconomic variables and infrastructure factors. We go beyond simple analyses of penetration at the country level, to understand the microeconomics of computer and Internet use in rural India.